The Overview of Indonesia Coal Bed Methane Resources - Edy Nursanto; Shofa Rijalul Haq; Inmarlinianto Inmarlinianto (Journal of Metallurgical Engineering and Processing Technology, 2024)
Coal Bed Methane (CBM) is generated by coal layers, there is a preceding process, which is the formation of coal (coalification). Coalification begins with the burial of organic material originating from plants. The burial, lasting hundreds of millions of years, results in increasing temperatures and pressures, causing physical and chemical changes to the organic material. Methane gas, the largest component of CBM, is formed. Two processes: biogenic and thermogenic. In the early stages of coalification, biogenic methane gas is produced as a byproduct of the activities of decomposing microorganisms (anaerobic bacteria), similar to what occurs in the decomposition of organic waste.  Only about 5 to 20 percent is stored within coal. There are four mechanisms for gas storage in coal: absorption, adsorption, free gas, and gas dissolved in water.  Among these four mechanisms, adsorption is the most significant, accounting for 98 percent of the stored CBM in a combined system of micropores (coal matrix) and cleats. Coal Bed Methane resources in Indonesia can be found across South Kalimantan, East Kalimantan, Sumatra, and Java.